Georgics of Ground Water Quality and Its Geogenic Management in Coastal Odisha; India - Mishra, Siba Prasad (Advanced Aspects of Engineering Research Vol. 4, 2021)
Odisha, an agrarian state along east coast of India has seven districts behind 480 km coast of Bay of Bengal. Agriculture and livelihood in Odisha is impossible without rain and ground water. Hoary capricious use of water for irrigation and water supply is orthodox and unethical. Inland anthropogenic stress and salinity intrusion of highly populated coastal districts has made ground water unfit for agriculture along the coastal areas. Yield augmentation is intricately allied with quality of the aquifer geometry, ground water, flow regime and its quality. Coastal Odisha is ?14700 km2 area, and accommodating ?1.26 mi people extending ?20-25 Km inland. The land cover of mangroves, sodden crops, alluvial flora, waterlogged swamps, deciduous forests, and sandy dunes is allowing six anastomosed river system to debouch Bay of Bengal. The edaphic factors demand upgrading of brackish water in its aquifers. The physicochemical parameters like pH, alkalinity, electrical conductivity, values of dissolved ionic constituents (Na+, Mg++, Ca++,K+) of its wells/tube wells water used for irrigation are studied for the years 2009-2014, Rainfall (2008-2020), flow through rivers and the yield of paddy. The Water quality indices like Sodium absorption ratio, Kelly’s index, and Permeability Index and many others of the collected underground water are calculated to discuss their suitability for use as irrigation water in the area and found safe. The Various water management strategies are studied, and ongoing moderation procedures are reflected so that the ground water of coastal Odisha can be fruitfully used for irrigation.